Food for the soul: the dynamics of fishing and fish consumption in Anglo-Saxon England: c. A.D. 410-1066 - Reynolds, Rebecca Virginia (2015)
The taste for fish in England and the British Isles as a whole has fluctuated on several occasions and understanding the reasons behind these changes is vital, especially in light of the great importance fish held in later medieval diet and society. The beginnings of marine fishing have usually been thought to lie in the late Anglo-Saxon period and are believed to lie with economic changes. Indeed, most studies of fish in archaeology have centred around economic approaches. However it is extremely unlikely for economics to have been the sole reason. This thesis will attempt to fill in the gap currently extant in early medieval fish studies by taking a multidisciplinary approach to exploring the character of fishing and fish consumption in Anglo-Saxon England. Zooarchaeological data alongside isotope evidence, artefactual, structural and textual will be considered together to explore not just economic but also social factors, in effect, exploring the dynamics of fishing and fish consumption. This multidisciplinary approach will also hopefully highlight the fact that fish cannot just be studied in isolation; to gain a full understanding of the implications freshwater and marine fishing will have on communities and society as a whole all aspects of fishing must be considered.